JNK signaling mediates wing form polymorphism in brown planthoppers (Nilaparvata lugens). (June 2016) - Lin, Xinda; Xu, Yili; Yao, Yun; Wang, Bo; Lavine, Mark D.; Lavine, Laura Corley
Abstract: Wing polyphenism is considered to be an adaptive trade-off between migration (long winged forms) and reproduction (short winged forms), determined by various environmental conditions. The c-Jun NH2-terminal kinase (JNK) is crucial for the regulation of the activity of a number of transcription factors, and is activated under stress and environmental fluctuations where it functions in maintaining cell viability and proliferation. We used RNA interference and a pharmacological inhibitor of JNK to test the role of JNK signaling in regulating the wing dimorphism of the brown planthopper, Nilaparvata lugens . Silencing NlJNK increased the proportion of short winged female adults, reminiscent of the effect of silencing inhibitory components of the insulin-signaling pathway, such as NlAkt . However, silencing of the JNK -activated transcription factors NlJun and NlFos did not change the wing form ratio significantly, indicating that NlJNK may not act through NlJun and NlFos in mediating this process. In summary, JNK signaling may play a role in determining wing polymorphism in N. lugens females. Graphical abstract: Highlights: Down-regulation of NlJNK by RNAi, or injection of JNK inhibitor CC-401, increases the proportion of short winged females. Down-regulation of the NlJNK targets NlJun or NlFos by RNAi had no effect on wing morph. Simultaneous down-regulation of NlFOXO and NlJNK resulted in an increase of the short winged morph compared with NlFOXO RNAi alone.